Who wants democracy ? - Alam, Javeed (New Delhi, 2006)
This book explores the working of democracy in India. Beneath the play of caste and communal politics, and the threats of institutional collapse, the author sees democracy acquiring a firm basis within Indian society. He shows what the voting patterns tell us about the links between regional voices and national unity, between the politics of community and the idea of citizenship, between the commitments of the poor and the apathy of the rich.
Keywords: Democracy